Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan pada Perusahaan Tembakau Tbk di Bursa Efek Indonesia Tahun 2019–2023 - Sikona, Barto; Johannes Baptista Halik; Claudio Julio Mongan (Politeknik Kampar, 2025)
This study analyzes the financial performance of tobacco companies listed on the Indonesia Stock Exchange for the 2019-2023 period using financial ratio analysis. The ratios used include liquidity, solvency, activity, and profitability. The results showed that the liquidity ratio decreased, with the Current Ratio falling to 63.94% in 2023, indicating potential difficulties in meeting short-term obligations. In contrast, the solvency ratio improved, marked by a decrease in the Debt to Equity Ratio (DER) from 80.50% in 2020 to 40.82% in 2023, indicating lower dependence on debt. Activity ratios also showed improved efficiency, with total asset turnover rising to 54% in 2023. In terms of profitability, Return on Assets (ROA) increased to 4.81% and Net Profit Margin (NPM) reached 8.87%, indicating better financial management. Overall, the company experienced fluctuations in financial performance, with challenges on liquidity but improvements on solvency, activity, and profitability. These findings can be taken into consideration for investors and management in financial decision-making.